2014
DOI: 10.7860/jcdr/2014/6996.3917
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Its Associated Factors Using WHOQOL- BREF Among Elderly in Urban Puducherry, India

Abstract: Background: Quality of Life (QOL) among elderly is a neglected issue especially in developing countries including India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
88
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 17 publications
26
88
5
1
Order By: Relevance
“…Similar results were seen in study done by Ganesh et al and Barau et al showing that gender had no influence on QOL. 8,10 Literate hypertensives had better scores compared to illiterates hypertensives in SAB, AUT, PPF, INT domains similar results were seen in study done by Ganesh et al showing that literacy had an impact on QOL however in Barau et al study revealed no difference among literate and nonliterates. 8,10 Married participants had better scores in SAB domain with divorced/separated/widow participants which was statistically significant similar results were seen in Ganesh et al 8 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were seen in study done by Ganesh et al and Barau et al showing that gender had no influence on QOL. 8,10 Literate hypertensives had better scores compared to illiterates hypertensives in SAB, AUT, PPF, INT domains similar results were seen in study done by Ganesh et al showing that literacy had an impact on QOL however in Barau et al study revealed no difference among literate and nonliterates. 8,10 Married participants had better scores in SAB domain with divorced/separated/widow participants which was statistically significant similar results were seen in Ganesh et al 8 …”
Section: Discussionsupporting
confidence: 77%
“…In the study done by Ganesh et al which used WHO QOL BREF questionnaire, showed no difference among hypertensive and non-hypertensive participants in physical, psychological and social domain which was similar to the present study. 8 Study done by Kaliyaperumal et al which used short form 36 item health survey questionnaire showed difference only in vitality domain and physical aspects and rest of domains aspects and rest of aspects were least affected. 9 The present study showed male hypertensives comparatively had better scores in AUT, PPF, DAD domains compared with females however there was no statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…[2] This finding was corroborated with a study conducted by Kumar et al on QOL of elderly in urban Puduchery in 2013. [3] They found that older age was associated with poor QOL. In another study conducted by Lokare et al, they found that QOL was significantly better among young people.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study has contrasted with a published study in India which has given lowest score in the social domain. (Kumar, Majumdar, & Pavithra, 2014). This could be as a result of the elderly in Yala province stayed with family members.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies suggests that people with higher level of education are more likely to engage in healthy behaviors which could improve physical health compared to those with lower level of education (Kumar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%